The Effect of Single-Session Stimulating Massage on the Knee Joint Position Sense in Healthy Older Adult Men: A Randomized Crossover Trial - Akramzadeh , Mahmood; Hosseini, Seyed Majid; Khalkhali Zavieh, Minoo; Khademi-Kalantari, Khosro; Akbarzadeh Baghban , Alireza (International Journal of Therapeutic Massage & Bodywork, 2024)
Background: Proprioception is critical for older adults to maintain their balance and prevent falling. However, massage is a convenient intervention that its beneficial effect on the proprioception is suggested. Purpose: This study aimed to determine whether one session of stimulating massage of the muscles around the knee joint improves position sense in older adult men. Methods: Twenty healthy older adults participated in this blind, randomized, crossover trial. The two treatment phases were massage and rest. The washout period between interventions was a 1-week interval. The massage protocol was as follows: deep effleurage, petrissage, and tapotement for 5 minutes for the anterior (tensor fascia lata, quadriceps, sartorius, and gracilis) and posterior (ham-strings) muscles of the knee (10 minutes in total). Results: Outcome measures were absolute, constant, and variable errors (AE, CE, and VE). Participants were assessed immediately before and after the intervention by a blinded investigator. Independent t-tests were used for statistical analyses. Massage reduced absolute error (2.77°, p = 0.01). Conclusion: The finding of this study confirms the beneficial impact of the massage on the joint position sense in healthy older adult men.